2020
DOI: 10.21512/bbr.v11i2.6193
|View full text |Cite
|
Sign up to set email alerts
|

Improving Organizational Citizenship Behavior through Job Satisfaction, Leader-Member Exchange, and Work-Life Balance

Abstract: The research aimed to analyze the effect of leader-member exchange, work-life balance, and job satisfaction on organizational citizenship behavior (OCB). The respondents were nursing staff at a hospital in Indonesia. The sample was 169 respondents, taken using a purposive sampling technique. Structural Equation Modeling (SEM) method was applied as the data analysis techniques with the application AMOS 22.0. Based on the results, the research finds that first, leader-member exchange and work-life balance have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
4
11
1
11
Order By: Relevance
“…However, job satisfaction does not affect OCB. This is different from previous research which concludes that job satisfaction has positive implications (Fitrio et al, 2019;Heriyadi et al, 2020;P Prasetio et al, 2017;Yuliani & Katim, 2017). This research, however, does not support the implications of job satisfaction on implementing positive behavior through OCB, but it indirectly increases OCB with a percentage of 15%.…”
Section: Discussioncontrasting
confidence: 99%
“…However, job satisfaction does not affect OCB. This is different from previous research which concludes that job satisfaction has positive implications (Fitrio et al, 2019;Heriyadi et al, 2020;P Prasetio et al, 2017;Yuliani & Katim, 2017). This research, however, does not support the implications of job satisfaction on implementing positive behavior through OCB, but it indirectly increases OCB with a percentage of 15%.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with Hypothesis 2, and in line with the findings of [97], the study findings depicts positive and strong association between WLB and job satisfaction as the balance between work and personal liabilities diminish the amount of strain and job dissatisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…Job satisfaction is one of the most important antecedents of organizational citizenship behavior (OCB) variable. Heriyadi et al (2020) and Nurjanah et al (2020) conducted studies on the effect of job satisfaction on OCB. They found that job satisfaction has a positive effect on OCB.…”
Section: Job Satisfaction and Organizational Citizenship Behaviormentioning
confidence: 99%